2021
DOI: 10.1001/jamanetworkopen.2021.24116
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With SARS-CoV-2 Infection Among Farmworkers in Monterey County, California

Abstract: Key Points Question What are the risk factors associated with SARS-CoV-2 infection among farmworkers in California? Findings In this cross-sectional study of 1107 farmworkers, both household and workplace risk factors, including living with children aged 5 years or younger or unrelated roommates and living or working with an individual with known or suspected COVID-19, were associated with positive results on transcription-mediated amplification tests and i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 33 publications
3
29
1
Order By: Relevance
“…Even the occupations that we generally associate with outdoor work, like agriculture and construction, can put workers into close contact within poorly ventilated spaces, such as in produce packing sheds, indoor construction sites, and vehicles. Furthermore, a study of agricultural workers found working outdoors and working in the fields to be risk factors for SARS-CoV-2 infection, perhaps because a lower perceived risk of outdoor work affected behavior or practices [ 47 ]. Thus, the conditions of work in these high-mortality occupations may have created opportunities for workplace exposure to SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Even the occupations that we generally associate with outdoor work, like agriculture and construction, can put workers into close contact within poorly ventilated spaces, such as in produce packing sheds, indoor construction sites, and vehicles. Furthermore, a study of agricultural workers found working outdoors and working in the fields to be risk factors for SARS-CoV-2 infection, perhaps because a lower perceived risk of outdoor work affected behavior or practices [ 47 ]. Thus, the conditions of work in these high-mortality occupations may have created opportunities for workplace exposure to SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we show that approximately half of the 1334 workers tested positive for anti-SARS-CoV-2 nucleocapsid antibodies at study enrollment (June–December 2020). The high proportion of seropositivity is similar to SARS-CoV-2 burden estimates among agricultural workers in the U.S. and underscores the risks such essential workers take in maintaining food supplies during pandemics [ 8 , 9 ]. It also demonstrates that during a time in which non-pharmaceutical interventions were widely implemented across Guatemala, such as physical distancing measures, school closures, and masking, essential workers remained at risk of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 89%
“…While there is a growing body of literature using active COVID-19 case-surveillance and mortality data to estimate the burden of COVID-19 among agricultural workers [ 2 , 6 , 7 ], few serosurveys have reported on the risk of SARS-CoV-2 infections within this population [ 8 , 9 ]. Active surveillance with molecular testing is useful to identify acute COVID-19, but can underestimate the risk of SARS-CoV-2 infection and confound analyses of risk factors, if not coupled with serology [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Daily scenarios experienced by produce industry workers were categorized into "indoor" and "outdoor" work scenarios (Figure 1) based on the activity-specific differences and risk profiles of each worker population and industry expert input. For example, while both indoor and outdoor workers engage in shared transportation to and from work 19,[43][44][45] , the specific mode of transportation (i.e., shared car [indoor] or bus [outdoor]) was determined through conversations with produce industry managers and farmworker extension specialists. For an indoor susceptible worker, we assumed that 2 h would be spent in shared car transportation, followed by a 12 h shift in an indoor produce packaging facility (11 h working, 1 h break), and 10 h in private housing.…”
Section: Sequential Work Scenarios For An Indoor and Outdoor Produce ...mentioning
confidence: 99%